ISTIRATIJIYAT AL-TA’ALUM AL-MUBASYIR LADA AL-THALABAH AL-MUTAKHASHISHIN FI AL-LUGHAH AL-‘ARABIYAH BI ISTIKHDAM BARNAMAJ ATLAS.ti - Taufik bin Ismail; Muhammad Sabri bin Sahrir; Aliff Fahmi bin Abdullah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
Learning strategy is a way to help students at mastering language and assimilate with it successfully.The studentsusing certain strategies inlanguage learning, will learn more effectively. This research was aimed to identify the direct strategies used by Arabic language students while learning the language in the International Islamic University Malaysia (IIUM). This research depended on qualitative research method by using a semi-structured interview protocol as a mean for data collection, and the participants were selected from students of Advanced Arabic language course at the International Islamic University Malaysia in 1stsemester, 2014/2015. The ATLAS.ti was used for data analysis; then, this research discovered (26) twenty-six direct learning strategiesused by the learnersin learning Arabic language. The results of this research were beneficial in improving the level of learning Arabic language, andgood for the teachers to recognize the difficulties faced by their students while learning the Arabic language.DOI: 10.15408/a.v3i2.3679